THE USE OF YOUTUBE TUTORIAL VIDEOS TO IMPROVE STUDENTS’ SPEAKING SKILL AT THE SECOND GRADE STUDENTS OF SMA NEGERI 4 BULUKUMBA - Andi Eritme Yustika Abrar; Asdian aya (Universitas islam Negeri Alauddin Makassar, 2022)
The objective of the research is to find out does the use of YouTube tutorial videos can improve the students’ speaking skill at the second grade students of SMA Negeri 4 Bulukumba. The researcher applied pre-experimental with pre-test and post-test design. The population of this research was taken by purposive sampling technique from the second grade students’ of SMA Negeri 4 Bulukumba in academic year 2020/2021. This population consists of 11 students. The result of the data analysis showed that there is a significant difference between pre-test and post-test of the students’ speaking skill especially in students’ fluency and pronunciation after giving treatment. The students’ mean score in pre-test was 42,72 and post-test was 59,09. It showed that the students’ speaking skill in post-test was higher than the students’ pre-test. The t-test value was 4,50 and it was greater than t-table 2,228 at he level of significance (α) = 0,05 and degree of freedom (df) =11-1=10. It was found that the result of t-test value was greater than t-table (4,50>2,228). It means that hypothesis H0 was rejected and H1 was accepted. This research finds that the use of YouTube tutorial video could improve students’ speaking skill in procedure text especially in students’ fluency and pronunciation. The researcher expexcts that the use of YouTube tutorial video could be used by the teacher as one of the media in teaching and learning process especially in teaching speaking.